Respuesta :

when the first reaction equation is:

 N2(g) + O2(g) 
 2NO(g)

when Keq = the concentrations of the products / concentrations of the reactants

so, Keq1 = [NO]^2 / [N2][O2]

 4.2 x 10^-31 = [NO]^2/[N2][O2] .

and when we multiply this reaction coefficient by 2 so the equilibrium reaction equation is:

4 NO(g)
 2N2(g) + 2O2(g)

this is the reverse reaction equation of the first reaction multiply by 2. so,

Keq2 = [O2]^2[N]^2/[NO]^4 and

 Keq2= 1 / (Keq1)^2

Keq2 = 1/ (4.2 X10^-31)^2

            = 5,67·10⁶⁰

so, the value of Keq for the reaction below is 5.67 X 10^60